Resiliensi Akademik Mahasiswa MBKM : Bagaimana Peranan Self Regulated Learning dan Efikasi Diri? - Tazky, Amanda; Arifiana, Isrida Yul; Efendy, Mamang (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the relationship between self-regulated learning and self-efficacy with academic resilience among students participating in the Merdeka Belajar Kampus Merdeka (MBKM) program. The research utilized a quantitative method with a non-probability sampling technique, specifically quota sampling, involving 230 respondents. Data were collected using questionnaires based on a Likert scale.The results indicated a positive relationship between self-regulated learning and self-efficacy with academic resilience. Multiple regression analysis revealed that self-regulated learning (X1) and self-efficacy (X2) significantly correlated with academic resilience (Y), with R = 0.769, R² = 0.591, F = 163.849, and p < 0.01. Together, these variables explained 59.1% of the variance in academic resilience, while the remaining 40.9% was influenced by other unexamined factors. Thus, the higher a person's self-regulated learning and self-efficacy, the higher their academic resilience. Keyword: Self – efficacy; MBKM Students; Academic Resilience; Self Regulated Learning